Respostas
respondido por:
5
(2/3+1/2)-1/3 = (4/6+3/6)-2/6 = 7/6-2/6 = 5/6
(7/2+1/4+1)-3/8 = (28/8+2/8+8/8)-3/8 = (30/8+8/8)-3/8 = 38/8-3/8 = 35/8
(2/3+1/2)-1/2 = (4/6+3/6)-3/6 = 7/6-3/6 = 4/6 = 2/3
(2-1/2)-(3/4-1/2) = (8/4-2/4)-(3/4-2/4) = 6/4-1/4 = 5/4
(7/2+1/4+1)-3/8 = (28/8+2/8+8/8)-3/8 = (30/8+8/8)-3/8 = 38/8-3/8 = 35/8
(2/3+1/2)-1/2 = (4/6+3/6)-3/6 = 7/6-3/6 = 4/6 = 2/3
(2-1/2)-(3/4-1/2) = (8/4-2/4)-(3/4-2/4) = 6/4-1/4 = 5/4
respondido por:
0
Resposta:
NAO ENTEDI
Explicação passo-a-passo:
DESCUPA
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás